“Porto Arte”: an authorized biography - Brites, Blanca (PORTO ARTE: Revista de Artes Visuais, 2013)
The article shows the history of “Porto Arte”, published by the Graduate Program in Visual Arts from Universidade Federal do Rio Grande do Sul (PPGAV/UFRGS). It offers remarks on the aspects of its formal developments since its first edition in 1990.